Computational analysis of heat transfer and fluid flow characteristics in a diamond microchannel heat sink with orthogonal ribs - Liang Du; Wenbo Hu; Ningkang Deng; Zhaoyang Zhang; Hongxing Wang (Case Studies in Thermal Engineering)
As electronic devices advance toward higher power densities and increased miniaturization, the resulting rise in heat flux presents significant challenges to their performance, reliability, operational lifespan, and energy efficiency. Effective thermal management technologies ensure that electronic equipment operates under optimal conditions, extends its service life, improves system integration and reliability, and ensures compliance with industry regulations and standards. Microchannel heat sinks are gaining increasing attention as an efficient thermal management solution. This study systematically analyzes the thermo-hydraulic characteristics of diamond microchannel heat sinks with various rib types (rhombic transverse rib, rhombic vertical rib, and rhombic orthogonal rib) and shapes (circular orthogonal rib, rhombic orthogonal rib, forward triangular orthogonal rib, reverse triangular orthogonal rib, and square orthogonal rib) using numerical simulations performed in COMSOL Multiphysics 6.0. The results indicate that rhombic transverse ribs and rhombic vertical ribs only disrupt the fluid flow in a single direction, whereas rhombic orthogonal ribs not only disturb the fluid in both transverse and vertical directions but also increase the solid-liquid contact area, thereby significantly enhancing heat transfer performance. However, the orthogonally arranged ribs complicate the fluid flow path and increase flow resistance, leading to a higher pressure drop. Compared to the transverse rib and vertical rib microchannel heat sinks, the heat transfer coefficient of the orthogonal rib microchannel heat sink increases by 182.8 % and 17.9 %, respectively, while the pressure drop rises by 1000.5 % and 17.5 %, respectively. The square orthogonal rib microchannel heat sink achieves an exceptional balance between pressure drop and heat transfer coefficient, resulting in the best comprehensive performance. Following that, the reverse triangular orthogonal rib microchannel heat sink, forward triangular orthogonal rib microchannel heat sink, and rhombic orthogonal rib microchannel heat sink demonstrated progressively lower comprehensive performance, with the circular orthogonal rib microchannel heat sink exhibiting the lowest comprehensive performance. In the square orthogonal rib microchannel heat sink, both the pressure drop and heat transfer coefficient increase with the enlargement of rib width. When the rib width is 0.4, the performance evaluation coefficient reaches 1.92. Therefore, the unique rib arrangement design of the orthogonal rib microchannel heat sink not only optimizes fluid flow and enhances heat transfer capacity but also effectively addresses the heat dissipation challenges of electronic devices. It serves as an ideal thermal management solution for modern high-power, high-density integrated electronic devices.